DEVELOPMENT AND LIBERALIZATION OF THE ECONOMY IN UZBEKISTAN - Saitov, Sirojiddin; Akhrorov, Elyorjan (Science technology&Digital finance, 2023)
The article covers feedback and measures taken on how relevant the liberalization of the economy in our country is and what reforms are possible through its development.